Optimization of Literacy Development for Children in Tanjung Kasau Plantation Village - Siringoringo, Yan Batara; Marpaung, TJ; Hasibuan, Citra Dewi; Tarigan, E.D.; Balqis, Muthia Ferliani; Sari, Aminah; Hasibuan, Mhd. Nasir; Siregar, Rosman (Talenta Publisher, 2023)
Reading is the most basic ability as a provision to learn everything. In literacy, reading is a very interesting and important form of learning for teachers and students so that learning is easy to understand or understand when doing reading activities. Literacy is a person's ability to process and understand information when carrying out the process of reading and writing. School is an institution that is responsible for creating a reading culture which is an important part of learning activities. Schools must be able to facilitate various means that can increase students' interest in reading, namely by utilizing the school library. Through reading students can broaden horizons, sharpen ideas, and increase knowledge. The method used in this activity is to teach students to read in groups by utilizing the books in the library of SDN 10 Tanjung Kasau plantation village. The results obtained from this program are being able to develop children's interest in reading and elementary school children's knowledge in reading, especially grades 1-4 who cannot read, so that the purpose of holding this interest in reading (literacy) program can be implemented.